2014
DOI: 10.1371/journal.pone.0102387
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Function of Periodontal Ligament Fibres in Orthodontic Tooth Movement

Abstract: Orthodontic tooth movement occurs as a result of resorption and formation of the alveolar bone due to an applied load, but the stimulus responsible for triggering orthodontic tooth movement remains the subject of debate. It has been suggested that the periodontal ligament (PDL) plays a key role. However, the mechanical function of the PDL in orthodontic tooth movement is not well understood as most mechanical models of the PDL to date have ignored the fibrous structure of the PDL. In this study we use finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 46 publications
1
44
0
9
Order By: Relevance
“…By contrast, the formation of bone tissue can be explained by fibre stretching . The maximum value of the maximal principal stresses can be found in the apical region of the PDL (see Figure A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the formation of bone tissue can be explained by fibre stretching . The maximum value of the maximal principal stresses can be found in the apical region of the PDL (see Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…[74][75][76] By contrast, the formation of bone tissue can be explained by fibre stretching. [77][78][79] The maximum value of the maximal principal stresses can be found in the apical region of the PDL (see Figure A2A). The over-elongation of fibres in this region causes fibrous network damage ( Figure 7C), local vascularization, 69 and mechanobiological signals (arachidonic acid metabolites, neuropeptides, or cytokines).…”
Section: Pdl Materials Model Application To the Microct Fe Modelmentioning
confidence: 97%
“…Deformation and stresses are mediated between teeth and bone by the PDL . Injury to the PDL is thought to play an important role in the mechanisms of tooth trauma and tooth mobility . Displacement, which was also demonstrated on teeth adjacent to the impacted incisor, can interrupt vascular blood supply and cause pulp necrosis which is one of the predisposing factors for inflammatory root resorption …”
Section: Discussionmentioning
confidence: 99%
“…24 Injury to the PDL is thought to play an important role in the mechanisms of tooth trauma and tooth mobility. 25 Displacement, which was also demonstrated on teeth adjacent to the impacted incisor, can interrupt vascular blood supply and cause pulp necrosis which is one of the predisposing factors for inflammatory root resorption. 26,27 The 10 m/s velocity of impact was based on previous studies in which bicycle accidents were shown to be common causes for dental trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and other mammals, such mechanoreceptors that are sensitive to local mechanical stimuli (e.g. encoding information on the hardness and stiffness of an item being bitten) are found in the periodontal ligament that surrounds the tooth root and suspends it in the socket (Hannam, 1969;Yamaguchi et al, 2012;McCormack et al, 2014). Lizards do not possess a periodontal ligament, but similar mechanoreceptors are almost certainly present in the dentine (Dong et al, 1985;Dong et al, 1993;Kieser et al, 2009;Kieser et al, 2011) and less certainly in the pulp cavity (Paphangkorakit and Osborn, 1997;Paphangkorakit and Osborn, 1998), jaw joints (Curtis et al, 2010b), skull sutures , bones (Jacobs and van Steenberghe, 1993) and soft tissues of the mouth, such as the tongue (Paphangkorakit and Osborn, 1998 Fig.…”
Section: Discussion Biting Substratementioning
confidence: 99%